De la “redundancia” a la “transparencia”: los avatares de una idea de la verdad - Albisu Aparicio, María (Revista de Filosofía, 2007)
We reconstruct the internal dialectic which leads from a deflationist position about truth – which is based on the “redundancy” of truth – to a inflationist position – supported on a certain interpretation of truth as a device of “disquotation”.
Keywords: Truth; Minimalism; Redundancy; Disquotation